DENSITY PERTURBATIONS IN A REALISTIC UNIVERSE - Demianski, M.; Golda, Z.; Woszczyna, A. (Одеські астрономічні публікації, 2017)
We analyze evolution of density perturbations in a flat or open universe filled in with matter, relativistic particles and possibly cosmological constant. Density perturbations grow very slowly in a universe filled in with low mass neutrinos.